2020
DOI: 10.1021/acs.langmuir.0c03222
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Films with Enhanced Corrosion Resistance and Self-Cleaning Performance on an Al Alloy

Abstract: In this article, a novel and facile method is used to construct superhydrophobic surfaces on aluminum alloys. A solution of aluminum chloride hexahydrate and N-dodecyltrimethoxysilane (DTMS) in ethanol was used as the electrolyte solution. The hydrolysis of DTMS was accelerated during the electrodeposition process, and the hydrolysate was bonded to a pretreated aluminum surface. The prepared aluminum alloy sample exhibits both superhydrophobicity (the surface water contact angle reached 155°) and excellent cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 75 publications
(132 reference statements)
0
25
0
Order By: Relevance
“…In a recently published paper by Zihao He et al, aluminum chloride hexahydrate and N-dodecyltrimethoxysilane (DTMS) in ethanol was used as electrolyte solution for the fabrication of a superhydrophobic surface with WSCA 155 • and 99.9% corrosion resistance when immersed inside a 3.5 wt% NaCl solution. This excellent anticorrosion behavior remained above 98% even after 30 days of immersion [76].…”
Section: Electrodepositionmentioning
confidence: 80%
“…In a recently published paper by Zihao He et al, aluminum chloride hexahydrate and N-dodecyltrimethoxysilane (DTMS) in ethanol was used as electrolyte solution for the fabrication of a superhydrophobic surface with WSCA 155 • and 99.9% corrosion resistance when immersed inside a 3.5 wt% NaCl solution. This excellent anticorrosion behavior remained above 98% even after 30 days of immersion [76].…”
Section: Electrodepositionmentioning
confidence: 80%
“…Many research efforts have been focused on the fabrication of hydrophobic metal surfaces by lowering their surface energy via chemical treatments (e.g., fluorinated silane), as well as increasing surface roughness (e.g., micro–nano hierarchical structure). As also observed in natural structures, penguins’ body seldomly adheres ice or frost even in the coldest environment because their feathers contain micro–nano rough hierarchical structures, which promote hydrophobicity . In these hierarchical structures, a large amount of trapped airbags are formed within the micro–nano bulges; thus, liquid droplets are difficult to wet the surface .…”
Section: Introductionmentioning
confidence: 99%
“…The surfaces were damaged after 400 grit SiC sandpaper abrasion under 16 kPa for 110 cm. He et al 15 demonstrated superhydrophobic aluminum surfaces through electrodeposition, and superhydrophobicity was lost after sliding against a 600 grit SiC sandpaper for 60 cm. Wang et al 25 constructed superhydrophobic surfaces on stainless steel by laser microprocessing.…”
Section: Introductionmentioning
confidence: 99%
“…Superhydrophobic materials, which can impede the spreading of water droplets, have shown enormous potential in a wide range of applications. Studies have demonstrated various superhydrophobic coatings that are preliminarily utilized in self-cleaning, , anti-icing, antifouling, energy harvesting, , drag reduction, droplet transporting, anticorrosion, and other aspects, yielding great industrial application value. The superhydrophobic surface refers to a solid surface with a static water contact angle greater than 150° .…”
Section: Introductionmentioning
confidence: 99%